Lentivirus‐Mediated Overexpression of MicroRNA‐210 Improves Long‐Term Outcomes after Focal Cerebral Ischemia in Mice - Zeng, Li‐Li (CNS Neurosci Ther, 2016)
AIMS: MicroRNAs play an important role in the pathogenesis of ischemic brain injury and in the repair process during postischemic condition. However, the key miRNAs and their function in these processes remain unclear. METHODS: Circulating blood MicroRNAs profiles were examined in the ischemic stroke patients. The predicted network of difference was analyzed by ingenuity pathway analysis. The key MicroRNAs were selected, and the function was further studied in a mouse ischemia model. The predicted downstream target was confirmed. RESULTS: We found that 24 MicroRNAs were differently expressed in stroke patients compared to the control (P < 0.05). Bioinformatic analysis showed a MicroRNAs regulated network with the highest score in the stroke cascade, which was consisted of 10 MicroRNAs including key hypoxia‐related miR‐210 and its predicted downstream target brain derived neurotrophic factor (BDNF). Lentivirus‐mediated miR‐210 overexpression enhanced the microvessel density and the number of neural progenitor cells in the ischemic mouse brain (P < 0.05) and improved neurobehavioral outcomes in the ischemic mouse (P < 0.05). MiR‐210 upregulation increased mBDNF/proBDNF protein expression in the normal and ischemic mouse brain. The dual‐luciferase reporter assay identified that BDNF was the direct target of miR‐210. CONCLUSION: MiR‐210 is a crucial ischemic stroke‐associated MicroRNAs and a potential target for the stroke therapy.